Oxide, electrolyte composition, and electricity storage device

By adopting oxides with specific crystal structures, the manufacturing process of lithium-ion batteries is simplified, the complex manufacturing process in the prior art is solved, and high ion conductivity and high efficiency manufacturing are achieved.

CN119631146APending Publication Date: 2025-03-14NITERRA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380057506.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-03
Filing Date
2023-07-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art requires precise control of material preparation and firing methods to stabilize cubic crystals, resulting in complex manufacturing processes.

Method used

By using an oxide having a garnet-type crystal structure containing Li, La and Zr, whose crystal structure includes at least two tetragonal crystal phases with different lattice constants, and the occupancy of Li at 8a is less than 95%, the manufacturing process is simplified.

Benefits of technology

The high ion conductivity oxide is manufactured through simple methods, and the performance and manufacturing efficiency of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119631146A_ABST
    Figure CN119631146A_ABST
Patent Text Reader

Abstract

Provided are an oxide, an electrolyte composition, and an electricity storage device that can be produced by a simple method. The oxide has a garnet-type crystal structure containing Li, La, and Zr, and the crystal structure contains at least two tetragonal crystal phases having different lattice constants. The crystal structure belongs to space group I41 / acd, and the occupancy of Li at the 8a-position of at least one tetragonal crystal phase may be 95% or less. The oxide may contain Sr. The electrolyte composition and the electricity storage device contain the oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an oxide having a garnet-type crystal structure containing Li, Zr and La, an electrolyte composition and an electricity storage device. Background Art

[0002] Oxides having a garnet-type crystal structure containing Li, Zr, and La have high chemical stability and lithium ion conductivity. For example, Li7La3Zr2O 12 (hereinafter referred to as LLZ) is an oxide that is stable to Li metal and theoretically exhibits 10 -4 S / cm to 10 -3 S / cm high ion conductivity. The crystal structure of LLZ mainly exists in cubic and tetragonal crystals. For LLZ, the tetragonal crystal with low ion conductivity is stable at room temperature, and the tetragonal crystal is transformed into a 10 -4 Cubic crystals with an ion conductivity of S / cm or more. In order to obtain an oxide showing high ion conductivity at room temperature, in the prior art disclosed in Patent Document 1, a specific element constituting LLZ is replaced with another element to stabilize the cubic crystal.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-40767 Summary of the invention

[0006] Problems to be solved by the invention

[0007] In order to stabilize the cubic crystal, the prior art requires precise control of material preparation, sintering and other methods to produce oxides.

[0008] The present invention has been made to solve the above problems, and an object of the present invention is to provide an oxide, an electrolyte composition, and a power storage device that can be produced by a simple method.

[0009] Methods used to solve problems

[0010] A first means for achieving the object is an oxide having a garnet-type crystal structure containing Li, La, and Zr, wherein the crystal structure includes at least two tetragonal phases having different lattice constants.

[0011] A second embodiment is that, in the first embodiment, the crystal structure belongs to the space group I41 / acd, and the occupancy of Li at the 8a position of at least one tetragonal phase is 95% or less.

[0012] A third aspect is the first aspect or the second aspect, further comprising Sr.

[0013] A fourth aspect is an electrolyte composition comprising the oxide according to any one of the first to third aspects.

[0014] A fifth aspect is an electric storage device including two or more electrode layers and a separator separating the two or more electrode layers, wherein at least one of the two or more electrode layers and the separator includes the oxide of any one of the first to third aspects.

[0015] A sixth aspect is an electric storage device comprising two or more electrode layers including a current collecting layer and a separator separating the two or more electrode layers, wherein the device comprises a protective layer arranged between the electrode layer and the separator or on the current collecting layer, and the protective layer comprises the oxide of any one of the first to third aspects.

[0016] Effects of the Invention

[0017] The oxide, electrolyte composition and power storage device according to the present invention can be produced by a simple method. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a cross-sectional view of the power storage device according to the first embodiment.

[0019] Figure 2 This is a diagram schematically showing the crystal structure of conventional tetragonal LLZ.

[0020] Figure 3 FIG. 1 is a diagram schematically showing the arrangement of Li in one crystal plane of a conventional tetragonal LLZ.

[0021] Figure 4 FIG2 is a diagram schematically showing the arrangement of Li in one crystal plane of an oxide.

[0022] Figure 5 It is a cross-sectional view of the power storage device according to the second embodiment.

[0023] Figure 6 It is a cross-sectional view of the power storage device according to the third embodiment. DETAILED DESCRIPTION

[0024] Hereinafter, preferred embodiments of the present invention will be described with reference to the drawings. Figure 1 Schematic cross-sectional view of the power storage device 10 of the first embodiment. The power storage device 10 of this embodiment is a lithium ion solid battery (secondary battery) in which the power generation element is composed of a solid. The power generation element is composed of a solid means that the skeleton of the power generation element is composed of a solid, including a method in which a liquid is impregnated in the skeleton.

[0025] The power storage device 10 includes, in order, a positive electrode layer 11, an electrolyte layer 14, and a negative electrode layer 15. The positive electrode layer 11, the electrolyte layer 14, and the negative electrode layer 15 are housed in a case (not shown).

[0026] The positive electrode layer 11 is formed by stacking a current collecting layer 12 and an active material layer 13. The current collecting layer 12 is a conductive member. Examples of the material of the current collecting layer 12 include metals selected from Ni, Ti, Fe and Al, alloys containing two or more of these elements, stainless steel, and carbon materials.

[0027] The active material layer 13 includes an electrolyte composition containing an oxide 18 and an active material 19. In order to reduce the resistance of the active material layer 13, a conductive additive may be included in the active material layer 13. Examples of the conductive additive include carbon black, acetylene black, Ketjen black, carbon fiber, Ni, Pt, and Ag.

[0028] Examples of active material 19 include metal oxides containing transition metals, sulfur-based active materials, and organic active materials. Examples of metal oxides containing transition metals include metal oxides containing one or more elements selected from Mn, Co, Ni, Fe, Cr, and V, and Li. Examples of metal oxides containing transition metals include LiCoO2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiMn2O4, LiNiVO4, LiNi 0.5 Mn 1.5 O4、LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O4 and LiFePO4.

[0029] In order to suppress the reaction between the active material 19 and the oxide 18, a coating layer may be provided on the surface of the active material 19. Examples of the coating layer include Al2O3, ZrO2, LiNbO3, Li4Ti5O 12 , LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4 and Li2MoO4.

[0030] Examples of sulfur-based active materials include S, TiS2, NiS, FeS2, Li2S, MoS3, and sulfur-carbon composite materials. Examples of organic active materials include free radical compounds represented by 2,2,6,6-tetramethylpiperidinyloxy-4-yl methacrylate and polytetramethylpiperidinyloxy vinyl ether, quinone compounds, radialene compounds, tetracyanoquinodimethane, and 5-oxyphenazine.

[0031] The electrolyte layer 14 includes an electrolyte composition containing an oxide 18. The electrolyte layer 14 is a separator that separates the positive electrode layer 11 and the negative electrode layer 15 and electrically insulates them from each other. The electrolyte layer 14 may contain an electrolyte solution obtained by dissolving an electrolyte salt in a solvent, and a binder. The solvent of the electrolyte solution is not particularly limited as long as it is a solvent that dissolves the electrolyte salt. Examples of the solvent include carbonates, aliphatic carboxylates, phosphates, γ-lactones, ethers, nitriles, sulfolane, dimethyl sulfoxide, fluorinated solvents, and ionic liquids. It may be a mixture thereof.

[0032] The binder is not particularly limited as long as it is a material that can bind the oxide 18. Examples of the binder include fluororesins, polyolefins, polyimides, polyvinyl pyrrolidone, polyvinyl alcohol, cellulose ethers, and rubber polymers such as styrene-butadiene rubber. Examples of the fluororesins include vinylidene fluoride polymers, polychlorotrifluoroethylene, polyvinyl fluoride, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers, tetrafluoroethylene-hexafluoropropylene copolymers, ethylene-tetrafluoroethylene copolymers, and ethylene-chlorotrifluoroethylene copolymers.

[0033] The negative electrode layer 15 is formed by stacking a current collecting layer 16 and an active material layer 17. The current collecting layer 16 is a conductive member. Examples of the material of the current collecting layer 16 include metals selected from Ni, Ti, Fe, Cu and Si, alloys containing two or more of these elements, stainless steel, and carbon materials.

[0034] The active material layer 17 includes an electrolyte composition containing an oxide 18 and an active material 20. In order to reduce the resistance of the active material layer 17, a conductive additive may be included in the active material layer 17. Examples of the conductive additive include carbon black, acetylene black, Ketjen black, carbon fiber, Ni, Pt, and Ag. Examples of the active material 20 include Li, Li-Al alloy, Li4Ti5O 12 , graphite, In, Si, Si—Li alloy, and SiO. Similar to the electrolyte layer 14 , the active material layers 13 and 17 may contain an electrolyte solution and a binder.

[0035] The power storage device 10 is manufactured, for example, in the following manner. For example, the power storage device 10 includes an electrolyte solution and a binder. An organic solvent in which a lithium salt is dissolved is mixed with the oxide 18, and a solution obtained by dissolving the binder in the solvent is mixed into the obtained mixture to prepare a slurry. After tape casting, it is dried to obtain a green sheet (electrolyte sheet) for the electrolyte layer 14.

[0036] An organic solvent in which a lithium salt is dissolved is mixed with an oxide 18, an active material 19 is mixed with the obtained mixture, and a solution obtained by dissolving a binder in the solvent is further mixed to prepare a slurry. After casting on the current collecting layer 12, it is dried to obtain a green sheet (positive electrode sheet) for the positive electrode layer 11.

[0037] An organic solvent in which a lithium salt is dissolved is mixed with an oxide 18, the resulting mixture is mixed with an active material 20, and further mixed with a solution in which a binder is dissolved in a solvent to prepare a slurry. After casting on the current collector 16, it is dried to obtain a green sheet (negative electrode sheet) for the negative electrode layer 15.

[0038] The electrolyte sheet, the positive electrode sheet and the negative electrode sheet are cut into specified shapes respectively, and then overlapped in the order of the positive electrode sheet, the electrolyte sheet and the negative electrode sheet, and crimped to each other to form an integrated whole. Terminals (not shown) are connected to the current collecting layers 12 and 16 respectively and sealed in a shell (not shown), thereby obtaining a storage device 10 including a positive electrode layer 11, an electrolyte layer 14 and a negative electrode layer 15. It should be noted that, of course, at least one of the positive electrode layer 11, the electrolyte layer 14 and the negative electrode layer 15 may not contain at least one of the electrolyte and the binder.

[0039] Regarding the crystal structure of oxide 18, the existing tetragonal Li7La3Zr2O 12 The crystal structure of (LLZ) will be described in comparison with the crystal structure of the oxide 18 of the present embodiment. Figure 2 This is a diagram schematically showing the crystal structure of 8 unit cells per chemical formula unit of the existing tetragonal LLZ. A tetragonal crystal is a crystal in which the lengths a and b of two of the three orthogonal edges of the unit cell are equal, and the length c of the other edge is different from a and b. The existing tetragonal LLZ has Li at the three ion positions of 8a, 16f, and 32g. The 8a position is tetrahedral coordinated, and the 16f and 32g positions are octahedral coordinated. The occupancy of Li at the 8a, 16f, and 32g positions is approximately 100%.

[0040] Figure 3 : is a diagram schematically showing the arrangement of Li in one crystal plane of the existing tetragonal LLZ. The Li existing in the ion site of the 8a position exists at the intersection of the ion conduction path. In the Li ion conduction path, the Li existing in the ion site of the 16f position and the 32g position are arranged between the Li existing in the ion site of the 8a position. Since the occupancy rate of Li at the 8a position is almost 100%, there is almost no vacancy at the intersection of the ion conduction path. Therefore, for the existing tetragonal LLZ, the ion conductivity caused by the movement of Li ions to the vacant position is reduced. The ion conductivity of the existing tetragonal LLZ at room temperature is generally 10 -6 The order of magnitude is S / cm.

[0041] Figure 4 This is a diagram schematically showing the arrangement of Li in one crystal plane of oxide 18 (tetragonal LLZ). The crystal structure of oxide 18 belongs to space group I41 / acd. In oxide 18, Li exists at four ion sites, namely, 8a, 16f, 32g, and 16e. Li existing at the ion sites of 8a and 16e exist at the intersection of the ion conduction path. In the Li ion conduction path, Li existing at the ion sites of 16f, 32g, and 16e are arranged between the Li existing at the ion site of 8a. The 8a and 16e sites are in tetrahedral coordination, and the 16f and 32g sites are in octahedral coordination. The ion conductivity of oxide 18 at room temperature is more than 100 times the ion conductivity of the existing tetragonal LLZ at room temperature. -4 S / cm or above.

[0042] The oxide 18 includes at least two tetragonal phases having different lattice constants. The one having a larger lattice constant ratio a / c of ​​the two tetragonal phases is referred to as a "first phase", and the one having a smaller ratio a / c is referred to as a "second phase". For example, a / c of ​​the first phase is within a range of 1.003 to 1.03, and a / c of ​​the second phase is within a range of 1.001 to 1.01.

[0043] The occupancy of Li at the 8a position of the first phase of oxide 18 is greater than the occupancy of Li at the 8a position of the second phase. The occupancy of Li at the tetrahedral coordination position including the 8a position and the 16e position of the first phase is greater than the occupancy of Li at the tetrahedral coordination position including the 8a position and the 16e position of the second phase.

[0044] It is inferred that the second phase, which has a relatively small occupancy rate of Li at the tetrahedral coordination position of the ion site including the 8a position and the 16e position, mainly plays the role of conducting Li ions, and the first phase, which has a relatively large occupancy rate of Li at the tetrahedral coordination position of the ion site including the 8a position and the 16e position, mainly plays the role of supplying Li ions. The first phase and the second phase are in such a complementary relationship, so it is inferred that oxide 18 has high ion conductivity.

[0045] The occupancy rate of Li at the 8a position of the second phase is preferably more than 30% and less than 95%. This is because, if the occupancy rate is less than 95%, the probability of vacancies existing at the intersection of the ion conduction path increases, so the ion conductivity generated by the movement of Li ions to the position of the vacancy increases. If the occupancy rate is more than 30%, it is not easy to produce electrical repulsion between vacancies, so the mobility of Li ions can be ensured. The occupancy rate of Li at the 8a position is more preferably more than 50%. If the occupancy rate of Li is less than 50%, the ratio of vacancies becomes more, and due to the electrical repulsion between vacancies, the mobility of Li ions decreases, and it can be seen that the tendency of ion conductivity reduction is reduced.

[0046] The 16e position is an ion position whose energy level is easily changed by composition. If the 16e position is stabilized, Li moves from other ion positions to the 16e position, and the occupancy rate of the 16e position becomes higher. The occupancy rate of Li at the 16e position of the first phase and the second phase is preferably less than 60% (except 0%). If the occupancy rate exceeds 60%, the mobility of the Li ions is reduced due to electrostatic repulsion with adjacent Li ions. The occupancy rate of Li at the 16e position is preferably more than 20%. When the occupancy rate of Li is less than 20%, it means that the 16e position is in an unstable state, it is difficult to produce Li ion conduction via the 16e position, and the ionic conductivity is reduced.

[0047] Li present in 16f position and 32g position has the effect of maintaining crystal structure and ensuring carrier concentration. The occupancy of Li at 16f position and 32g position of the first phase and the second phase is preferably 50% or more (including 100%), more preferably 75% or more. This is because, if the occupancy of Li at 16f position and 32g position is less than 75%, it can be seen that the carrier concentration is reduced and the ionic conductivity is reduced. This is because, if the occupancy is less than 50%, it can be seen that the tendency of the crystal structure to be destroyed due to the electrostatic repulsion caused by the continuous presence of vacancies.

[0048] The lattice constants of the first phase and the second phase and the occupancy of Li at each ion site can be obtained by obtaining a powder neutron diffraction spectrum and analyzing the diffraction spectrum using the Rietveld method. The interplanar spacing d of the crystal phase analyzed by powder neutron diffraction and the Rietveld method ranges from 0.5 to 4.7 Å. The analysis using the Rietveld method uses data from powder neutron diffraction with a resolution Δd / d of less than 0.16%. The analysis using the Rietveld method is based on the following prerequisites: the crystal structure belongs to the space group I41 / acd, has two tetragonal phases with different lattice constants, and Li can exist at the 8a position, 16f position, 32g position, and 16e position.

[0049] Even without performing analysis using powder neutron diffraction and the Rietveld method, it is possible to easily infer that oxide 18 includes two tetragonal phases having different lattice constants by powder X-ray diffraction and the Rietveld method. As a characteristic of the tetragonal phase, it can be cited that in the X-ray diffraction pattern, the Bragg reflection of the (800) plane is divided into two peaks due to the difference in the plane spacing. Oxide 18 has a Bragg reflection of the (800) plane in the X-ray diffraction pattern that is divided into three peaks, and it is inferred that peaks from two or more crystal phases overlap.

[0050] Whether the oxide 18 contains two tetragonal crystals can be inferred by assuming that there are two tetragonal phases belonging to the space group I41 / acd and having a lattice constant of a>c, and calculating the lattice constant using the Rietveld method. If the ratio a / c of ​​the lattice constants of the two assumed tetragonal crystals converges to a value greater than 1.001, it can be inferred that the oxide 18 contains two tetragonal phases with different lattice constants.

[0051] The crystal structure of oxide 18 is a tetragonal crystal with a lattice constant close to that of a cubic crystal, and the difference between a and c of the unit cell is small. Therefore, when the lattice constant is obtained by powder X-ray diffraction, a powder X-ray diffraction device with high angular resolution is required. The powder X-ray diffraction device preferably uses radiated light as a light source. As a benchmark for the angular resolution of the powder X-ray diffraction device, when the standard sample LaB6 (NIST SRM660c) is measured at a wavelength of 0.85Å, the half-peak width of the Bragg reflection of the (110) plane must be less than 0.030°.

[0052] As oxide 18, for example, Li7La3Zr2O substituted with other elements can be cited. 12 (LLZ) is an oxide of a part of the constituent elements, or an oxide to which other elements are added in a trace amount without replacing the constituent elements. As other elements, at least one element selected from the group consisting of Mg, Al, Si, Ca, Ti, V, Ga, Sr, Y, Nb, Sn, Sb, Ba, Hf, Ta, W, Bi, Rb and lanthanoids (excluding La) can be exemplified. The other element is preferably at least one of Mg and Sr, and Sr is particularly preferred.

[0053] Sr has an ionic radius close to that of La and is an element that easily replaces La in LLZ. If Sr replaces the La site, the Li concentration around Sr increases due to the difference in valence, which has the effect of improving the stability of the 16e site. When the amount of Sr replacement is appropriate, it helps to improve the ionic conductivity of oxide 18.

[0054] Mg is an element that forms a composite oxide with Li. When making LLZ, the raw materials are prepared in a way that Li is excessive in consideration of the volatilization of Li during firing. If Mg is added to the raw materials, when the excess Li is not sufficiently volatilized during firing, the remaining Li and Mg form a composite oxide. Since the interface resistance layer of lithium carbonate or the like formed by the excess Li can be reduced, the ion conductivity of the oxide 18 can be improved.

[0055] The oxide 18 can be manufactured by using a Li-containing compound, a La-containing compound, a Zr-containing compound, and a compound containing other elements (Mg, Sr, etc.) as required as starting materials, weighing and mixing the starting materials in a manner to obtain a desired chemical composition, and sintering. The oxide 18 is a polycrystalline material. The sintered body containing the oxide 18 can be made into the electrolyte layer 14. The powder of the oxide 18 after pulverizing the sintered body can also be arranged in the electrolyte layer 14, the active material layers 13, and 17.

[0056] The electrolyte layer 14 and the active material layers 13 and 17 may contain one or more other solid electrolytes in addition to the oxide 18. Other solid electrolytes include crystalline and amorphous oxide-based solid electrolytes such as perovskite-type, NASICON-type, and LISICON-type, and hydride-based solid electrolytes.

[0057] Examples of perovskite-type solid electrolytes include oxides containing at least Li, Ti, and La, such as La 2 / 3- X Li 3X As NASICON-type solid electrolytes, oxides containing at least Li, M (M is one or more elements selected from Ti, Zr and Ge) and P, such as Li(Al,Ti)2(PO4)3 and Li(Al,Ge)2(PO4)3, can be cited. As LISICON-type solid electrolytes, Li 14 Zn(GeO4)4. As hydride-based solid electrolytes, there can be exemplified solid electrolytes that are hydrides of alkali metals or alkaline earth metals and contain at least one of the 13th group elements (e.g., B, Al, Ga, In, Ta) of the 18th group periodic table. For example, LiBH4 and LiAlH4 can be cited.

[0058] Reference Figure 5The second embodiment is described. In the first embodiment, the case where the oxide 18 is used in a secondary battery in which the power generation element is composed of a solid is described. In the second embodiment, the case where the oxide 18 is used in a liquid lithium ion battery in which an organic solvent is used as the electrolyte is described. The same reference numerals are given to the same parts as those described in the first embodiment, and the following description is omitted. Figure 5 It is a cross-sectional view of an electric storage device 21 according to the second embodiment.

[0059] The power storage device 21 includes a positive electrode layer 11, a separator 22, and a negative electrode layer 15 in this order. They are housed in a housing (not shown). The separator 22 is durable to the active materials 19, 20, and the electrolyte contained in the positive electrode layer 11 and the negative electrode layer 15, and is composed of a porous body that allows lithium ions to pass but does not have electronic conductivity. As the separator 22, non-woven fabrics and porous films composed of cellulose, polypropylene, polyethylene, etc. can be exemplified.

[0060] Since the electricity storage device 21 of the second embodiment contains the oxide 18 in the positive electrode layer 11 and the negative electrode layer 15 , the oxide 18 can be produced by a simple method similar to the electricity storage device 11 of the first embodiment.

[0061] Reference Figure 6 The third embodiment is described. In the first and second embodiments, the case where the oxide 18 is included in the positive electrode layer 11, the electrolyte layer 14, and the negative electrode layer 15 is described. In the third embodiment, the case where the oxide 18 is included in the protective layers 26 and 29 is described. The same reference numerals are given to the same parts as those described in the first and second embodiments, and the following description is omitted. Figure 6 It is a cross-sectional view of an electric storage device 23 according to the third embodiment.

[0062] The power storage device 23 includes a positive electrode layer 24, a separator 22, and a negative electrode layer 27 in this order. These are accommodated in a case (not shown). The power storage device 23 is a liquid lithium ion battery using an organic solvent as an electrolyte.

[0063] The current collecting layer 12 and the active material layer 25 are stacked on the positive electrode layer 24. The active material layer 25 contains the active material 19. In order to reduce the resistance of the active material layer 25, the active material layer 25 may contain a conductive additive such as carbon black, acetylene black, Ketjen black, carbon fiber, Ni, Pt, and Ag.

[0064] A protective layer 26 is disposed between the separator 22 and the negative electrode layer 27 . The protective layer 26 includes an oxide 18 .

[0065] In the negative electrode layer 27, an active material layer 28, a protective layer 29 and a current collecting layer 16 are sequentially stacked. The active material layer 28 is composed of, for example, Li, Li-Al alloy, Li-Sn alloy, Li-Si alloy, Li-Mg alloy, Li-Si alloy or Si-Li alloy. The protective layer 29 contains an oxide 18. The protective layers 26 and 29 are configured by stacking sheets, coating on the separator 22 and the current collecting layer 16, etc.

[0066] Since the oxide 18 having a garnet crystal structure containing Li, La, and Zr has resistance to reduction to the metal lithium of the active material layer 28, the operating stability of the power storage device 23 is increased. In addition, the protective layer 26 interposed between the active material layer 28 and the separator 22 suppresses short circuits caused by dendrite growth of metal lithium. The protective layer 29 interposed between the active material layer 28 and the current collecting layer 16 suppresses deterioration of the current collecting layer 16.

[0067] Example

[0068] The present invention will be described in further detail by way of examples, but the present invention is not limited to these examples.

[0069] (Preparation of Oxides)

[0070] Li2CO3, La(OH)3 and ZrO2 were weighed in a manner to form the various theoretical composition formulas shown in Tables 1 and 2, and SrCO3 and MgO were weighed as needed. Considering the volatilization of Li during firing, Li2CO3 was excessive by about 15 mol% in element conversion. The weighed raw materials and organic solvent were put into a nylon can together with zirconium oxide balls, and crushed and mixed for 15 hours using a ball mill. After the slurry was taken out of the can, it was dried and fired on a MgO plate at 900°C for 1 hour, and further fired on a MgO plate at 1200°C for 15 hours.

[0071] A binder was added to the fired powder, and the mixture was pulverized and mixed in an organic solvent using a ball mill for 15 hours. The slurry was taken out of the tank and dried to obtain a powder. The obtained powder was solidified into a disc-shaped particle with a diameter of 12 mm and a thickness of about 1.5 mm by compression molding, and then the particles were subjected to 1.5 t / cm by cold isostatic pressing (CIP). 2 The molded body is placed on a powder with the same composition as the molded body, sintered at a temperature above 1050°C for 3-36 hours in an inert gas atmosphere, and cooled at a rate of 10°C / min to obtain sintered bodies of various oxides with different compositions.

[0072] (Determination of ionic conductivity)

[0073] Using a symmetrical cell in which current collectors were brought into close contact with both surfaces of the obtained sintered body, the ion conductivity at 25° C. was measured by an alternating current impedance method.

[0074] (Identification of crystal structure and ion site occupancy)

[0075] The sintered body was wet-milled in a glove box with an argon atmosphere using a planetary ball mill and then dried to obtain powders of various oxides. The diffraction patterns of the oxides were obtained using a powder neutron diffraction device. Neutron diffraction was performed using the high-intensity proton accelerator BL20 of J-PARC, with an output power of 700 kW, a dual frame (DF), and a measurement time of 20 minutes.

[0076] In the diffraction spectrum obtained by the rear detector group with a d range of 0.181-5.09Å and a resolution of Δd / d: 0.15%, the ratio of the first phase to the second phase, the lattice constants (Å) of the first phase and the second phase, and the Li occupancy (%) of each ion position of the first phase and the second phase were obtained by the Rietveld method. The analysis software "Z-Rietveld" was used in the analysis using the Rietveld method, and the premise conditions were set as follows: the crystal structure belongs to the space group I41 / acd (tetragonal), there are two tetragonal phases (first phase and second phase) with different lattice constants, Li can exist at the 8a position, 16f position, 32g position and 16e position, the position occupancy of La, Zr, and O is 1, and the maximum value of the Li position occupancy is 1. The indicators of rationality were set as Rwp <15 and S <3.0.

[0077] The theoretical composition formula of the prepared oxide, the proportion of the first phase (mass %), the lattice constant of the first phase (Å), and the occupancy rate (%) of Li at each ion position of the first phase at the 8a position, 16f position, 32g position, and 16e position are recorded in Table 1. The theoretical composition formula of the oxide, the proportion of the second phase (mass %), the lattice constant of the second phase (Å), the occupancy rate (%) of Li at each ion position of the second phase at the 8a position, 16f position, 32g position, and 16e position, and the ionic conductivity (S / cm) are recorded in Table 2.

[0078] The theoretical composition formula of the oxide of Example 4 is the same as that of the oxide of Example 3. For the oxide of Example 4, the ratio of the first phase to the second phase, the lattice constant, and the Li occupancy were determined, but the ionic conductivity was not measured. The ionic conductivity was set to 1.0×10 -3 S / cm or more was judged as "A", and the ion conductivity was 1.0×10 -4 S / cm or more and less than 1.0×10 -3 S / cm was judged as "B", and the ion conductivity was less than 1.0×10 -4S / cm was judged as "C".

[0079] [Table 1]

[0080]

[0081] [Table 2]

[0082]

[0083] As shown in Table 1, the crystal structure of the oxides of Comparative Examples 2 and 4 is a cubic crystal with equal lattice constants a, b, and c. The crystal structure of the oxides of Comparative Examples 1 and 3 is a single tetragonal crystal (space group I41 / acd) with equal lattice constants a and b and c shorter than a, and there are no two tetragonal phases with different lattice constants. As shown in Table 2, the ion conductivity of Comparative Examples 1-4 was determined to be C.

[0084] The crystal structure of the oxide of Examples 1 to 5 has two tetragonal phases (first phase and second phase) with different lattice constants. In each example, the proportion (mass %) of the first phase is greater than the proportion (mass %) of the second phase, and the ratio a / c of ​​the lattice constant of the first phase is greater than the ratio a / c of ​​the lattice constant of the second phase.

[0085] In each embodiment, the occupancy of Li at the 8a position of the first phase is greater than the occupancy of Li at the 8a position of the second phase, and the occupancy of Li at the tetrahedral coordination position including the 8a position and the 16e position of the first phase is greater than the occupancy of Li at the tetrahedral coordination position including the 8a position and the 16e position of the second phase. In Examples 1-5, the occupancy of Li at the 8a position of the second phase is 30% or more and 95% or less, and the occupancy of Li at the 16e position of the first phase and the second phase is 60% or less (except 0%).

[0086] The ion conductivity of Examples 1-5 was determined as A or B. As can be seen from this, the oxide having two tetragonal phases (first phase and second phase) with different lattice constants showed a 1.0×10 -4 High ion conductivity of more than S / cm.

[0087] In Examples 1-5, the sintered body of the oxide was obtained by placing the molded body on a powder having the same composition as the molded body and firing it, and then cooling it at a rate of 10° C. / min. It is obvious that there is no need for a complicated operation such as covering the molded body with a powder having the same composition as the molded body during firing as in the prior art, and thus an oxide showing high ion conductivity can be produced by a simple method.

[0088] As mentioned above, although this invention was demonstrated based on embodiment, this invention is not limited to the said embodiment at all, It can be easily guessed that various improvements and modifications can be made within the range which does not deviate from the summary of this invention.

[0089] In the embodiment, as the power storage device 10, a power storage device having a positive electrode layer 11 having an active material layer 13 provided on one side of a current collecting layer 12 and a negative electrode layer 15 having an active material layer 17 provided on one side of a current collecting layer 16 is described, but it is not necessarily limited to this. For example, in a power storage device having an electrode layer (so-called bipolar electrode) having active material layers 13 and 17 provided on both sides of a current collecting layer 12, each element of the embodiment can of course be applied. If the bipolar electrodes and the electrolyte layer 14 are alternately stacked and housed in a housing (not shown), a so-called bipolar structure power storage device can be obtained.

[0090] In the embodiment, the case where both active material layers 13 and 17 and electrolyte layer 14 include oxide 18 is described, but the present invention is not necessarily limited to this. It is sufficient for the power storage device to include oxide 18 at least one of active material layers 13 and 17 and electrolyte layer 14 .

[0091] In the third embodiment, the protective layer 26 is provided between the active material layer 28 and the separator 22 and the protective layer 29 is provided between the current collecting layer 16 and the active material layer 28, but the present invention is not necessarily limited thereto. Of course, either the protective layer 26 or 29 may be omitted.

[0092] In the embodiment, the oxide 18 is described by taking the storage devices 10, 21, and 23 including lithium ion batteries as examples, but the invention is not necessarily limited thereto. Other storage devices including the oxide 18 include electrochemical capacitors using redox reactions of electrodes, redox reactions of ions in an electrolyte, double-layer electrochemical capacitors, and metal-air batteries using oxygen in the air as a positive electrode active material.

[0093] Explanation of symbols

[0094] 10, 21, 23 Energy storage devices

[0095] 11, 24 positive electrode layer (electrode layer)

[0096] 12.16 Collector Layer

[0097] 13. 17 Active material layer (electrolyte composition)

[0098] 14 Electrolyte layer (electrolyte composition, separator)

[0099] 15, 27 negative electrode layer (electrode layer)

[0100] 18 Oxide

[0101] 22 Diaphragm

[0102] 26, 29 protection layer

Claims

1. An oxide having a garnet-type crystal structure containing Li, La and Zr, wherein: The crystal structure includes at least two tetragonal phases having different lattice constants.

2. The oxide according to claim 1, wherein The crystal structure belongs to space group I41 / acd, The occupancy of Li at the 8a position of at least one of the tetragonal phases is 95% or less.

3. The oxide according to claim 1 or 2, wherein It also contains Sr. 4 . An electrolyte composition comprising the oxide according to claim 1 or 2 .

5. An electric storage device comprising two or more electrode layers and a separator separating the two or more electrode layers, wherein: At least one of the two or more electrode layers and the separator includes the oxide according to claim 1 or 2.

6. An electric storage device comprising two or more electrode layers including a current collecting layer and a separator separating the two or more electrode layers, wherein: A protective layer is provided between the electrode layer and the separator or on the current collecting layer, The protective layer comprises the oxide according to claim 1 or 2.

Citation Information

Patent Citations

  • Lithium ion-conductive ceramic material and lithium battery

    JP2016040767A